Задачи по элементарной математике - Лидский В. Б. Виктор Борисович; Овсянников Л. В. Лев Васильевич; Тулайков А. Н. Анатолий Николаевич; Шабунин М. И. Михаил Иванович (Москва, Наука, 1970)
Исключено из фонда НТБ ТПУ